Information and Communication Technology (ICT)–Based Educational Transformation in Indonesia: A Systematic Literature Review - Fathirma'ruf Fathirma'ruf; Asmedy Asmedy (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
This study aims to analyze the implementation of Information and Communication Technology (ICT) in formal education in Indonesia, particularly regarding trends in technology adoption, the types of technologies most commonly used, and their impact on learning effectiveness. The study employed a Systematic Literature Review (SLR) method based on the PRISMA guidelines, analyzing 100 articles indexed in the Scopus database. The findings indicate that ICT implementation is still predominantly concentrated at the higher education level, while early childhood and primary education remain relatively underdeveloped due to limitations in infrastructure and digital literacy. The most frequently utilized technologies include Augmented Reality (AR), Virtual Reality (VR), Learning Management Systems (LMS), and Artificial Intelligence (AI). Most studies highlight the positive impact of ICT on improving learning outcomes, conceptual understanding, and higher-order thinking skills (HOTS), as well as enhancing student motivation and participation through interactive technologies. However, the application of ICT in the psychomotor domain remains limited. These findings suggest that ICT-based educational transformation requires stronger support through the development of teachers’ competencies, equitable infrastructure distribution, and the selection of technologies aligned with pedagogical objectives.